Thermoplastic Polyurethane Blends With Thermal Energy Storage/Release Capability - Dorigato, Andrea; Rigotti, Daniele; Pegoretti, Alessandro (Frontiers in Materials, 2018)
In this work innovative the thermal energy storage materials were developed by encapsulating a paraffin having a melting temperature of 6 °C (M6D) in a thermoplastic polyurethane (TPU), and the most important physical properties of the resulting samples were investigated from a thermo-mechanical point of view. Field emission scanning electron microscope (FESEM) micrographs demonstrated a homogeneous microcapsules distribution and good interfacial adhesion with the TPU matrix even at elevated M6D concentrations. With a capsule concentration of 60 wt% it was possible to obtain elevated melting enthalpy values (up to 95 J/g), retaining the energy storage/release properties even after 50 thermal cycles. The hardness and the dimensional stability of the TPU matrix above its glass transition temperature were strongly increased upon M6D addition, but this stiffening effect was associated to a certain embrittlement. The investigated blends could be applied for winter sport application for low temperature thermal energy storage/release materials.